Nilai-nilai Keadilan dalam Ekonomi Syari'ah - Bustanul Arifin; Ilyas Nurul Azam (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2024)
Sharia Economy, which is based on Islamic principles, places justice as one of its core values. Through the prohibition of usury, the obligation of zakat, profit-sharing systems, and transparency in transactions, the sharia economy aims to create a fair distribution of wealth and equal treatment for all parties. Profit-sharing systems like mudharabah and musyarakah, as well as productive waqf programs, are concrete examples of how the principle of justice is applied to enhance community welfare and reduce economic disparity. Transparency and accountability in the sharia economy ensure that all transactions are conducted with integrity, increasing trust and stability in the financial system. These values of justice not only support the achievement of economic goals but also form the foundation for a fairer and more prosperous society. The sharia economy offers a sustainable and ethical alternative to the global economic system, emphasizing a balance between economic gain and social responsibility.